Identifikasi dan Kausalitas Dari Faktor Penyebab Perselingkuhan Di Kota Denpasar - Santiningsih, Ni Made; Kencana, I Putu Eka Nila; Sukarsa, I Komang Gde (Jurnal Matematika; Vol 12 No 1 (2022), 2022)
Infidelity can have an impact on married life, some examples of which are less harmonious relationships with partners, and divorce. Infidelity is a sexual and emotional activity carried out by one or both individuals bound by a committed relationship. This study aims to determine the causative factors of infidelity and the causative factors that dominate infidelity. The method used in this research is structural equation modeling partial least square (SEM-PLS). The place where this research was conducted is in Denpasar City with a research period of October to November 2021. Data were obtained based on a questionnaire in the form of responses from married residents to the factors causing infidelity. The questionnaires were distributed as many as 130 questionnaires. This study obtained the results that the factors that cause infidelity are sexual factors, emotional factors, love factors, and social factors. Infidelity occurs dominated by emotional factors, namely the lack of attention from partners.